(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes issues of lexical expression of quantitativeness in various languages. The methods of expressing quantitativeness in languages are diverse, with the most effective being lexical means. Lexical means of expressing quantitativeness differ depending on the characteristics of each language. This is assessed considering the lexical richness of the language, the internal structure of words, semantic features, and possibilities of their use. The article also examines studies on quantitativeness and its lexical expression, which are the subject of numerous researches, and based on these studies, conclusions are drawn about the lexical expression of quantitativeness.